2021
DOI: 10.1177/13524585211003291
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab treatment in Denmark: A national study based on the Danish Multiple Sclerosis Registry

Abstract: Objective: To investigate clinical outcomes in a real-world setting in the complete population-based cohort of alemtuzumab-treated MS patients in Denmark. Methods: Data were retrieved from The Danish Multiple Sclerosis Registry between 2009 and 2019. Demographic and disease-specific patient parameters related to treatment history, efficacy, and safety outcomes were assessed at baseline and during follow-up visits. Results: A total of 209 patients (78% female) started treatment with alemtuzumab during the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
3
10
1
Order By: Relevance
“…This is slightly higher compared to previous studies, specifically 39% in one study where alemtuzumab was the first line treatment (Cohen et al, 2012;Coles et al, 2011) and 32% with alemtuzumab as the second line treatment (Center et al, 2012). Another study reported that EDSS remained stable in 68% of patients, and 75% of patients were relapse-free at two years, but did not report the combined NEDA status (Theodorsdottir et al, 2021). Finally, one study found that 80% stayed free from relapses and 93% stayed free from disability accumulation at two years (Kalincik et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is slightly higher compared to previous studies, specifically 39% in one study where alemtuzumab was the first line treatment (Cohen et al, 2012;Coles et al, 2011) and 32% with alemtuzumab as the second line treatment (Center et al, 2012). Another study reported that EDSS remained stable in 68% of patients, and 75% of patients were relapse-free at two years, but did not report the combined NEDA status (Theodorsdottir et al, 2021). Finally, one study found that 80% stayed free from relapses and 93% stayed free from disability accumulation at two years (Kalincik et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Between 2009 and 2019, only 167 RRMS patients in Denmark received alemtuzumab for ≥2 year. (Theodorsdottir et al, 2021). Previous studies have included more patients (29 patients (Gilmore et al, 2020), 85 (Harding et al, 2019), 189 (Kalincik et al, 2017), 215 (Coles et al, 2011)), but implementation of article 20 from the European Medical Agency restricted the use of alemtuzumab (European Medicines Agency, 2019), and consequently the pool of potential patients for the study resulted in reduced recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that patients switching from fingolimod to ocrelizumab were more likely to experience suboptimal disease control and worsening of disability throughout the washout period and during a follow-up period of 6 month [38][39][40]. Use of alemtuzumab as successor to fingolimod was repeatedly debated [28][29][30][31][32][33][34][35][36]. However, a large prospective cohort study confirmed impaired effectiveness and safety of this therapeutic switch [37].…”
Section: Discussionmentioning
confidence: 99%
“…Other qualitative changes in the immune network that may influence disease activity include transcriptomic changes of CD4 + T cells [61], the modulation of T helper cell phenotype balances and the increase in regulatory T cell abundance [62]. We speculate that these effects interfere with cell depletion and immune reconstitution in an unfavorable manner, resulting in increased risk for progression of disability [24,25,[28][29][30][36][37][38][39][40] and, perhaps in part, the development of secondary autoimmunity [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation